Zn < 2 + >-histidine coordination-based acid-sensitive dynamic hydrogel and preparation method thereof
Through GHHPH polypeptide modification and Zn2+ coordination technology, an acid-sensitive dynamic hydrogel was prepared, which solved the shortcomings of existing hydrogels in mechanical durability and biocompatibility, and achieved efficient self-healing and excellent antibacterial , anti-inflammatory properties.
Patent Information
- Application Number
- CN202411337557.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-02-11
AI Technical Summary
The existing dynamic hydrogels have shortcomings in mechanical durability and biocompatibility, and their self-healing conditions are harsh and their repair efficiency is low.
Histidylation and modification of hyaluronic acid through GHHPH polypeptide, and Zn2+ coordinates with histidine metal on the long chain of hyaluronic acid to form a crosslinking point based on ligand-metal coordination bonds to prepare an acid-sensitive type Dynamic hydrogel.
It improves the mechanical properties and self-healing properties of the hydrogel, while giving it excellent antibacterial and anti-inflammatory effects, and is suitable for biomedicine, tissue engineering and other fields.
Smart Images

Figure CN119409989A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of functional polymer material synthesis, and specifically relates to a Zn-based 2+ -Histidine-coordinated acid-sensitive dynamic hydrogel and preparation method thereof. Background Art
[0002] Hydrogel is an extremely hydrophilic three-dimensional cross-linked network polymer. Due to its good water solubility and adjustable physical and chemical properties, it has broad research and clinical application prospects in biomedical fields such as wound dressings, drug release, tissue engineering scaffolds, biosensors, and bio-inks. However, it also faces many problems in practical applications. For example, tissue regeneration and sustained drug release require materials that can be used for a long time, so mechanical durability has become an indispensable characteristic of such materials. Due to daily movement and injuries of the human body, implanted hydrogels are constantly subjected to mechanical forces, which may destroy the integrity of the cross-linked network structure, not only reducing its functional performance, but also increasing the risk of microbial invasion and infection. In order to meet such requirements, the researchers introduced dynamic covalent cross-linking strategies and non-covalent cross-linking strategies when preparing hydrogels, and designed dynamic hydrogels with self-healing injectable properties.
[0003] In recent years, the research on dynamic hydrogels has made great progress. Compared with traditional hydrogels, due to the dynamic reversible links in the hydrogel network, self-healing hydrogels can restore their original structure and function after injury, and can significantly reduce patients' discomfort, infection risk, recovery time and treatment costs. However, there are still limitations in hydrogel cross-linking strategies and usage conditions. For example, the hydrogel raw materials are of non-biological origin, have poor biocompatibility, and have potential biological toxicity, which is not conducive to biomedical applications. Secondly, some dynamic hydrogels have harsh self-healing conditions and low repair efficiency. Therefore, it is crucial to develop dynamic hydrogel materials with low biotoxicity and good self-healing injectable properties. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a Zn-based 2+ - Preparation method of histidine-coordinated acid-sensitive dynamic hydrogel.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a Zn-based 2+ - A method for preparing a histidine-coordinated acid-sensitive dynamic hydrogel, characterized in that: it comprises:
[0008] Dissolving hyaluronic acid and 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride in PBS buffer and stirring evenly to prepare a hyaluronic acid mixed solution;
[0009] Dissolve the GHHPH short peptide in deionized water to obtain a GHHPH short peptide solution;
[0010] The GHHPH short peptide solution was added to the hyaluronic acid mixture, stirred for reaction, dialyzed with deionized water, and freeze-dried to obtain the histidyl hyaluronic acid product;
[0011] The histidine hyaluronic acid product is dissolved in PBS, a ZnCl2 solution is added, and after being mixed evenly, the pH is adjusted to alkaline and stirred evenly to obtain the acid-sensitive dynamic hydrogel based on Zn2+-histidine coordination.
[0012] As a preferred embodiment of the preparation method of the present invention, the dosage of hyaluronic acid, 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride and PBS buffer is 990-1100 mg: 490-510 mg: 110-120 mL, the concentration of PBS buffer is 10 mM, and the pH is 7-7.5.
[0013] As a preferred embodiment of the preparation method of the present invention, the stirring time of the magnetic stirrer is 30 minutes.
[0014] As a preferred embodiment of the preparation method of the present invention, the dosage ratio of GHHPH peptide to deionized water in the GHHPH short peptide solution is 270-300 mg: 4-6 mL.
[0015] As a preferred embodiment of the preparation method of the present invention, the stirring reaction conditions are: reacting at 25-30°C for 18-24h.
[0016] As a preferred embodiment of the preparation method of the present invention, the dosage of ZnCl2 and deionized water in the ZnCl2 solution is 2.7 mg: 95-105 μL.
[0017] As a preferred embodiment of the preparation method of the present invention, the pH value of the NaOH solution is 10.
[0018] As a preferred embodiment of the preparation method of the present invention, the dosage of the histidine hyaluronic acid, PBS, ZnCl2 aqueous solution and NaOH solution is 39-41 mg: 390-410 μL: 95-105 μL: 150-200 μL.
[0019] Another object of the present invention is to overcome the deficiencies in the prior art and provide a Zn-based 2+ -Acid-sensitive dynamic hydrogel prepared by the preparation method of histidine-coordinated acid-sensitive dynamic hydrogel.
[0020] Another object of the present invention is to overcome the deficiencies in the prior art and provide a Zn-based 2+ -The invention discloses a method for preparing a histidine-coordinated acid-sensitive dynamic hydrogel and an application of the prepared acid-sensitive dynamic hydrogel in the construction of self-healing materials, injectable materials or controlled drug release materials.
[0021] Beneficial effects of the present invention:
[0022] (1) The present invention uses GHHPH polypeptide to modify hyaluronic acid by histidyl modification, and then Zn 2+ The metal of histidine on the long chain of hyaluronic acid is coordinated to form a cross-linking point based on the ligand-metal coordination bond, and the pH value of the hydrogel microenvironment is adjusted to prepare an acid-sensitive dynamic hydrogel with self-healing and injectable properties. The present invention prepares the hydrogel through reversible metal coordination interaction, the experimental conditions are mild, and the preparation process is simple, which not only improves the mechanical properties of the hydrogel, but also makes it have excellent self-healing and injectable properties. The imidazole group in histidine and Zn 2+ The introduction of , endows it with excellent antibacterial effect, as well as good anti-inflammatory effect.
[0023] (2) The present invention is based on histidine-Zn 2+ The coordination effect is used to construct an extracellular matrix (ECM)-like acid-sensitive dynamic hydrogel material with antibacterial and anti-inflammatory properties. The hydrogel material combines the high biocompatibility of ECM hydrogel, the antibacterial properties of the imidazole group in histidine, and Zn 2+ The immunomodulatory properties of dynamic hydrogels and the intelligent response characteristics of dynamic hydrogels have important application value in the fields of biomedicine, tissue engineering, wound healing, and intelligent drug release. At the same time, by further optimizing the preparation method and the formula of hydrogels, improving their performance and stability, more practical applications can be achieved, promoting technological progress and industrial applications in related fields. In the future, with the continuous development of materials science and biotechnology, Zn-based 2+-Histidine-coordinated acid-sensitive dynamic hydrogels are expected to play an important role in precision medicine, smart materials and environmental protection, and promote technological progress and industrial applications in related fields. Through interdisciplinary collaborative research, this new type of hydrogel material will be applied to more practical scenarios to achieve broader social and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0025] Figure 1 This is the sol-gel transition diagram of the hydrogel at different pH values in Example 3 of the present invention.
[0026] Figure 2 This is the SEM image of the hydrogel structure in Example 3 of the present invention.
[0027] Figure 3 is a dynamic performance diagram of the hydrogel in Example 3 of the present invention, wherein Figure 3 (a) self-healing performance; Figure 3 (b) Injectable properties.
[0028] Figure 4 This is the rheological properties diagram of the hydrogel in Example 3 of the present invention: Figure 4 (a) Dynamic frequency scanning of hydrogel; Figure 4 (b) Strain amplitude scan of the hydrogel; Figure 4 (c) Alternating strain scan of the hydrogel.
[0029] Figure 5 This is a degradation curve diagram of the hydrogel of Example 3 of the present invention at pH=8.5 and pH=6.8.
[0030] Figure 6 Graph showing the antibacterial properties of the hydrogel of the present invention; Figure 6 (a) shows the growth of S. aureus and E. coli after co-culture with bacteria; Figure 6 (b) SEM image of S. aureus and E. coli after co-culture of hydrogel and bacteria.
[0031] Figure 7 Graph showing the anti-inflammatory properties of the hydrogel in an embodiment of the present invention; Figure 7 (a) Immunofluorescence staining results of RAW 264.7 cells after co-culture with different hydrogel extracts: cell actin (green), M1 polarization marker iNOS (red), and cell nucleus (blue); Figure 7 (b) Immunofluorescence staining results of RAW 264.7 after co-culture with different hydrogel extracts: cell actin (green), M2 polarization marker Arg-1 (red), and cell nucleus (blue). DETAILED DESCRIPTION
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0033] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0034] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0035] The raw materials in the examples of the present invention are all commercially available unless otherwise specified, as shown in Table 1 for details.
[0036] Table 1
[0037]
[0038]
[0039] Example 1
[0040] (1) Synthesis of histidine hyaluronic acid
[0041] 1000 mg HA and 500 mg DMTMM were dissolved in 115 mL PBS buffer, stirred on a magnetic stirrer for 30 min, and then 300 mg GHHPH short peptide was dissolved in 5 mL deionized water and added thereto, stirred at room temperature for 24 h. After the reaction was completed, the mixture was dialyzed for 5 days and freeze-dried to obtain histidyl hyaluronic acid product.
[0042] (2) Based on Zn 2+ Preparation of acid-sensitive dynamic hydrogels coordinated by -histidine
[0043] 40 mg of the histidine hyaluronic acid obtained in step (1) was dissolved in 400 μL of PBS, and 100 μL of ZnCl2 solution was added thereto. After mixing evenly, 150 μL of NaOH with a pH value of 10 was added to adjust the pH to alkaline. After stirring evenly, an acid-sensitive dynamic hydrogel based on Zn2+-histidine coordination was finally obtained.
[0044] Example 2
[0045] (1) Synthesis of histidine hyaluronic acid
[0046] 990 mg HA and 490 mg DMTMM were dissolved in 110 mL PBS buffer, stirred on a magnetic stirrer for 30 min, and then 290 mg GHHPH short peptide was dissolved in 4 mL deionized water and added thereto, stirred at room temperature for 24 h. After the reaction was completed, the mixture was dialyzed for 5 days and freeze-dried to obtain histidyl hyaluronic acid product.
[0047] (2) Based on Zn 2+ Preparation of acid-sensitive dynamic hydrogels coordinated by -histidine
[0048] 39 mg of the histidine hyaluronic acid obtained in step (1) was dissolved in 390 μL of PBS, and 95 μL of ZnCl2 solution was added thereto. After mixing evenly, 180 μL of NaOH with a pH value of 10 was added to adjust the pH to alkaline. After stirring evenly, a Zn-based hyaluronic acid was finally obtained. 2 +-Histidine-coordinated acid-sensitive dynamic hydrogel.
[0049] Example 3
[0050] (1) Synthesis of histidine hyaluronic acid
[0051] 1100 mg HA and 510 mg DMTMM were dissolved in 120 mL PBS buffer, stirred on a magnetic stirrer for 30 min, and then 310 mg GHHPH short peptide was dissolved in 6 mL deionized water and added thereto, stirred at room temperature for 24 h. After the reaction was completed, the mixture was dialyzed for 5 days and freeze-dried to obtain histidyl hyaluronic acid product.
[0052] (2) Based on Zn 2+ Preparation of acid-sensitive dynamic hydrogels coordinated by -histidine
[0053] 41 mg of the histidine hyaluronic acid obtained in step (1) was dissolved in 410 μL of PBS, 105 μL of ZnCl2 solution was added thereto, and after mixing evenly, 200 μL of NaOH with a pH value of 10 was added to adjust the pH to alkaline, and after stirring evenly, a Zn-based hyaluronic acid was finally obtained. 2+ -Histidine-coordinated acid-sensitive dynamic hydrogel.
[0054] Figure 1 The acid-sensitive dynamic hydrogel prepared at different pH values undergoes sol-gel transition. It can be seen from the figure that the Zn 2+ The solution is added to the histidine hyaluronic acid solution, mixed evenly, the pH is adjusted to alkaline, and the solution quickly gels. Figure 2 This is the SEM image of the hydrogel. It can be seen from the figure that the prepared acid-sensitive dynamic hydrogel has a porous three-dimensional network microstructure.
[0055] Example 4
[0056] This example explores the preparation of Zn-based 2+ - The self-healing and injectable properties of histidine-coordinated acid-sensitive dynamic hydrogels, the specific steps are:
[0057] The prepared acid-sensitive dynamic hydrogel was placed in a polytetrafluoroethylene mold, and the square hydrogel was demolded to obtain the square hydrogel. It was cut into four pieces of equal size with a scalpel, and the four hydrogels were placed on a glass slide, two of which were stained with neutral crystal violet for easy observation. Let them contact each other, wait for 10 minutes, and observe their self-healing. Then the hydrogel was loaded into a syringe and injected with a 22G needle. At the same time, in order to reflect the remodelability of the hydrogel, the hydrogels were dyed separately and loaded into different syringes respectively, and then injected into the flower-shaped silicone mold, and demolded after standing for 10 minutes.
[0058] Figure 3 Based on Zn 2+ -The self-healing performance and injectable performance diagram of the acid-sensitive dynamic hydrogel coordinated by histidine; where a is the self-healing performance diagram and b is the injectable performance diagram; as shown in Figure a, the hydrogel is cut into 4 pieces. After the independent hydrogel pieces come into contact with each other, the damaged part can be quickly repaired within 5 minutes to form a complete hydrogel. After clamping one end of the hydrogel with tweezers, the hydrogel can be suspended in the air without breaking. By applying a certain tensile force at both ends, the hydrogel can be stretched and deformed, but no breakage occurs, which proves that the acid-sensitive dynamic hydrogel has good self-healing properties. The injected hydrogel can remain continuous and can be injected and shaped at will. After removing the mold, the hydrogel can still maintain its original shape without separation. The above results show that the prepared acid-sensitive dynamic hydrogel has good tensile properties, self-healing properties, and good injectable properties.
[0059] Example 5
[0060] This example explores the Zn 2+ -The mechanical properties of histidine-coordinated acid-sensitive dynamic hydrogels, the specific steps are:
[0061] Before testing, the dynamic hydrogel was made into a cylindrical sheet with a diameter of 10 mm and a thickness of 2 mm. The rheological properties of the hydrogel were determined using a rheometer. The specific steps of the rheological test are as follows: at 25°C, with a gap of 2 mm, the changes in the storage modulus (G') and loss modulus (G") of the hydrogel were observed when the shear frequency was dynamically changed from 0.1 to 100 rad / s. Then, the shear frequency was fixed at 1 rad / s, and the strain gradient was changed from 0.1% to 500% to determine the intersection of the G' and G" values, and its self-healing properties were further confirmed by observing the changes in G' and G" under alternating strains of 1% and 450%.
[0062] Figure 4 Based on Zn 2+ -The mechanical properties of the acid-sensitive dynamic hydrogel coordinated by histidine. Figure a shows the changes in G' and G" under shear frequencies ranging from 0.1rad / s to 100rad / s, where the value of G' is always higher than G", and G' remains almost unchanged with the increase of shear frequency, indicating that the hydrogel always maintains the state of elastic gel under different shear frequencies. Figure b shows that the change curves of G' and G" under strains from 0.1% to 450% intersect at 250%, proving that the hydrogel has undergone a sol-gel transition.
[0063] Figure c shows the changes in G' and G" under alternating strains of 1% and 270%. After several cycles, it was found that the G' and G" values were able to remain stable and close to the initial values, indicating that with the alternating changes in strain, the hydrogel can still maintain good self-healing properties. According to the above rheological test results, the hydrogel of the present invention has excellent mechanical properties and good self-healing properties.
[0064] Example 6
[0065] This example explores the Zn 2+ - Biodegradation performance of histidine-coordinated acid-sensitive dynamic hydrogel at different pH. The specific implementation steps are as follows:
[0066] After freeze-drying the prepared hydrogel, the initial weight was weighed and recorded as M0, and degradation experiments were carried out in PBS buffer at pH = 6.8 and pH = 8.5 at 37°C. After soaking for 24 hours, the hydrogel was taken out and freeze-dried, and the weight of the hydrogel after secondary freeze-drying was weighed and recorded as Mt. This step was repeated many times until the hydrogel was completely degraded. The calculation formula (1) of the degradation rate is as follows:
[0067]
[0068] Depend on Figure 5It can be seen that when pH = 6.8, the degradation rate of the hydrogel reaches 100% in about 2 days, and when pH = 8.5, the hydrogel is completely degraded on the 5th day. The experimental results show that the hydrogel degrades faster in a slightly acidic environment, proving that the hydrogel obtained in the present invention has good biodegradability and has great potential in the application of controlled drug release in an acidic environment.
[0069] Example 7
[0070] This example explores the Zn 2+ - Antibacterial properties of histidine-coordinated acid-sensitive dynamic hydrogel. The specific implementation steps are as follows:
[0071] The prepared hydrogel was cut into small pieces with a mass of 100 mg and placed in different test tubes, and 1 mL of 105 CFU / mL bacterial solution was added to each test tube, and then placed in a 37°C constant temperature shaker at 120 rpm for co-culture for 24 hours. After co-culture, the bacterial concentration was diluted to 104 CFU / mL, and 100 μL of the mixed bacterial solution after co-culture was evenly spread on the solid LB medium agar plate, and 3 agar plates were coated for each concentration. The control group was directly coated with a bacterial solution diluted with PBS buffer to a concentration of 104 CFU / mL. Then it was placed in an incubator at 37°C for 24 hours to evaluate the antibacterial properties of the hydrogel. Then 100 mg of hydrogel was placed in a 108 CFU / mL bacterial solution, with PBS solution as the control group, and co-cultured at 37°C for 12 hours. 10 μL of bacterial solution was dropped onto a silicon wafer from each group and fixed with 4% paraformaldehyde for 30 min. The wafers were then dehydrated with 30%, 50%, 70%, 90%, and 100% ethanol solutions, respectively, for 20 min at each concentration. After dehydration, the wafers were fixed on the sample stage with conductive glue, sprayed with gold, and characterized by SEM.
[0072] Depend on Figure 6 a It can be seen that the hydrogel exhibits a good antibacterial effect, with an antibacterial rate of more than 99%, and has a strong bactericidal effect; the imidazole group of histidine and Zn 2+ Form a stable coordination bond, Zn 2+ It can be evenly distributed in the hydrogel network, ensuring that its antibacterial effect is stably exerted throughout the hydrogel material. Figure 6 b shows that the morphology of the bacteria in the control group is intact through SEM observation, S. aureus presents a smooth small sphere, and E. coli presents a rod-shaped structure with blunt ends. The bacterial biofilm in the experimental group is damaged, the contents leak out, and the bacterial structure is obviously destroyed. Therefore, the hydrogel obtained in the present invention has excellent antibacterial properties.
[0073] Example 8
[0074] This example explores the Zn 2+- Anti-inflammatory properties of histidine-coordinated acid-sensitive dynamic hydrogel. The specific implementation steps are as follows:
[0075] In this experiment, the polarization behavior of macrophages was used to reflect the anti-inflammatory property of hydrogels. Immunofluorescence staining was used to detect the polarization behavior of macrophages, and the expression of M1 macrophage-related markers (iNOS) and M2 macrophage-related markers (Arg-1) was confirmed by staining.
[0076] 2×10 4 RAW 264.7 cells were seeded in 24-well plates. After incubation in the incubator for 8 hours, 10 μL of LPS was added to each well of the control group to stimulate the cells to polarize to the M1 phenotype. The culture medium of the experimental group was replaced with hydrogel extract, and 10 μL of LPS was also added to each well. After 8 hours of co-culture, the 24-well plate was precooled, rinsed twice with PBS, fixed with 4% paraformaldehyde overnight, punched with 0.1% Triton X-100 for 10 minutes, and then incubated with blocking solution at room temperature for 1 hour. 300 μL of primary antibody (anti-rabbit iNOS antibody and anti-rabbit Arg-1 antibody) was added to each well and incubated overnight at 4°C. After incubation, the primary antibody was recovered, and the cells were rinsed three times with PBS. 300 μL of secondary antibody (goat anti-rabbit secondary antibody Alexa 488) was added to each well and incubated at room temperature in the dark for 1 h. The secondary antibody was recovered, and the cells were rinsed three times with PBS. 200 μL of FITC-labeled phalloidin was added to stain the cytoskeleton for 30 min, and the cells were rinsed three times with PBS. Finally, the cell nuclei were counterstained with 4,6-diamino-2-phenylindole (DAPI) for 5 min. After rinsing three times with PBS, images were taken with an inverted fluorescence microscope.
[0077] Depend on Figure 7 a shows that the iNOS expression in the control group was high, and the cells were polarized to the M1 phenotype. However, iNOS in the hydrogel group was almost not expressed, which indicates that the hydrogel material effectively inhibited the polarization of macrophages to the M1 phenotype. On the contrary, Figure 7 As shown in b, Arg-1 was hardly expressed in the control group, while Arg-1 fluorescence was significantly expressed in the hydrogel group, showing anti-inflammatory properties, and the cells differentiated into M2 type, showing excellent anti-inflammatory effects.
[0078] Comparative Example 1
[0079] The difference from Example 1 is that no GHHPH short peptide is added;
[0080] 1000 mg HA and 500 mg DMTMM were dissolved in 115 mL PBS buffer, stirred on a magnetic stirrer for 30 min, and then stirred at room temperature for 24 h. After the reaction was completed, the mixture was dialyzed for 5 days and freeze-dried to obtain a modified hyaluronic acid product.
[0081] Dissolve 40 mg of the modified hyaluronic acid obtained in step (1) in 400 μL of PBS, add 100 μL of ZnCl2 solution, mix well, add 150 μL of NaOH with a pH value of 10, adjust the pH to alkaline, and stir well until it does not form a gel.
[0082] Comparative Example 2
[0083] The difference from Example 1 is that no ZnCl2 solution is added;
[0084] 1000 mg HA and 500 mg DMTMM were dissolved in 115 mL PBS buffer, stirred on a magnetic stirrer for 30 min, and then 300 mg GHHPH short peptide was dissolved in 5 mL deionized water and added thereto, stirred at room temperature for 24 h. After the reaction was completed, the mixture was dialyzed for 5 days and freeze-dried to obtain histidyl hyaluronic acid product.
[0085] Dissolve 40 mg of the histidine hyaluronic acid obtained in step (1) in 400 μL of PBS, mix well, add 150 μL of NaOH with a pH value of 10, adjust the pH to alkaline, and stir well until it does not form a gel.
[0086] Comparative Example 3
[0087] The difference from Example 1 is that the amount of 40 mg of histidine hyaluronic acid obtained in step (1) is replaced by 30 mg; no gelation occurs after adding ZnCl2 solution, no gelation occurs after adding NaOH dropwise, and no gelation occurs after adding excessive NaOH.
[0088] Comparative Example 4
[0089] The difference from Example 1 is that the amount of 40 mg of histidine hyaluronic acid obtained in step (1) is replaced by 35 mg; it does not form a gel after adding ZnCl2 solution, but forms a gel after adding NaOH dropwise. The gel is transparent and solidifies into white after a period of time and cannot heal itself.
[0090] Comparative Example 5
[0091] The difference from Example 1 is that the amount of 40 mg of histidine hyaluronic acid obtained in step (1) is replaced by 45 mg; it does not gel after adding ZnCl2 solution, but gels after adding NaOH dropwise, presenting a white colloidal solid. The gel is fragile and cannot self-heal.
[0092] Comparative Example 6
[0093] The difference from Example 1 is that the amount of 40 mg of histidine hyaluronic acid obtained in step (1) is replaced by 50 mg; it does not gel after adding ZnCl2 solution, but gels after adding NaOH dropwise, presenting a white colloidal solid, which is brittle and cannot self-heal.
[0094] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A Zn-based 2+ - A method for preparing a histidine-coordinated acid-sensitive dynamic hydrogel, characterized in that: include, Dissolving hyaluronic acid and 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride in PBS buffer and stirring evenly to prepare a hyaluronic acid mixed solution; Dissolve the GHHPH short peptide in deionized water to obtain a GHHPH short peptide solution; The GHHPH short peptide solution was added to the hyaluronic acid mixture, stirred for reaction, dialyzed with deionized water, and freeze-dried to obtain the histidyl hyaluronic acid product; The histidine hyaluronic acid product was dissolved in PBS, and ZnCl2 solution was added. After mixing evenly, the pH was adjusted to alkaline and stirred evenly to obtain the Zn-based 2+ -Histidine-coordinated acid-sensitive dynamic hydrogel.
2. The preparation method according to claim 1, characterized in that: The dosage of the hyaluronic acid, 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride and PBS buffer is 990-1100 mg: 490-510 mg: 110-120 mL, the concentration of PBS buffer is 10 mM, and the pH is 7-7.
5.
3. The preparation method according to claim 1, characterized in that: The stirring time of the magnetic stirrer is 30 min.
4. The preparation method according to claim 1, characterized in that: The dosage ratio of GHHPH peptide to deionized water in the GHHPH short peptide solution is 270-300 mg: 4-6 mL.
5. The preparation method according to claim 1, characterized in that: The stirring reaction is carried out at 25-30° C. for 18-24 hours.
6. The preparation method according to claim 1, characterized in that: The dosage relationship of ZnCl2 and deionized water in the ZnCl2 solution is 2.7 mg:95-105 μL.
7. The preparation method according to claim 1, characterized in that: The pH value of the NaOH solution is 10.
8. The preparation method according to claim 7, characterized in that: The dosage of the histidine hyaluronic acid, PBS, ZnCl2 aqueous solution and NaOH solution is 39-41 mg: 390-410 μL: 95-105 μL: 150-200 μL.
9. The acid-sensitive dynamic hydrogel prepared by the preparation method according to claims 1 to 8.
10. Use of the acid-sensitive dynamic hydrogel according to claim 9 in the construction of self-healing materials, injectable materials or controlled drug release materials.